Comparison of maternal and neonatal serum leptin levels in preeclampsia and normal pregnancy - Nesa Asnafi1; Majid Sharbatdaran; Karimollah Hajian (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Leptin is a protein product of obesity gene and is synthesized mainly by adipose tissue.Objective: The aim of this study was to determine maternal and neonatal serum leptin levels in term preeclamptic and normal pregnancies.Materials and Methods: This cross sectional study was performed on 37 preeclamptic and 40 normotensive term pregnant women without other disease. Serum level of leptin was measured in all of pregnant mothers and after delivery, their neonates. This study was performed in Babol Yahyanejad Hospital from March 2006 to December 2006.Results: Infants with preeclamptic mothers had significantly lower leptin level than control group (p=0.02). There was no significant difference in serum leptin levels between normal and preeclamptic women (p=0.749).Conclusion: According to the results, it would be concluded that leptin level in infants of preeclamptic mothers is lower than infants of normal mothers. This can only confirm the diagnosis of disease after birth but it cannot predict the preeclampsia.